The influence of standards and patents on long-term economic growth - Knut Blind; Florian Ramel; Charlotte Rochell (The Journal of Technology Transfer, 2021)
Formal standards codify knowledge. Next to patents representing the generation of innovative knowledge, standards can hence be used to proxy the diffusion of innovative knowledge in macroeconomic growth models. Previous work mainly investigates the positive impact of in particular patents, but also standards on economic growth in short term, single country studies. This study is the first to examine the long-term effects of formal standards and patents on economic growth in a panel of eleven EU-15 countries between 1981 and 2014 using panel cointegration techniques. From policy makers' perspective standardization has also gained recently an increasing attention, e.g. in the call for the development of a European standardization strategy in the update of the industrial strategy. Our results show that European and international standards foster growth for the group of countries but that national standards have ambiguous growth effects in the panel. For patents, no significant effect on growth in this group of countries is identified.
Keywords: O31; O33; O34; O47; 600; Economic growth; Standards; Patents; European Union; Panel cointegration